Solar-powered agricultural vehicles: Advancing sustainable farming in India - CHAUHAN, SUHANI; MITTAL, LALIT (The Indian Journal of Agricultural Sciences, 2025)
The solar-powered agricultural vehicle (420 cm × 188 cm) was designed and constructed during the years 2021–24 at Amity International School, Pushp Vihar, New Delhi, India to explore its development and potential impact in promoting sustainable agricultural practices in India. The vehicle, equipped with a 4.5 kWh solar panel system and a lithium iron phosphate (LiFePO4) battery (60 V, 72 Ah), generates and stores renewable energy for operation, reducing reliance on fossil fuels. Constructed from lightweight metals and featuring wide wheels for enhanced traction on uneven terrain, the vehicle is optimized for use in agricultural environments, with a cargo capacity of 400 kg. This study assesses the vehicle’s cost-effectiveness, low maintenance requirements, and environmental benefits, particularly its role in reducing carbon emissions and minimizing labour costs for farmers. By offering an alternative to traditional, fuel-powered machinery, the solar-powered farm vehicle helps lower greenhouse gas emissions and supports the transition toward more sustainable farming practices. The paper also discusses the broader implications for scaling solar-powered transportation in rural regions, energy independence for farmers and the role of renewable energy in addressing climate change. The findings suggest that solar-powered vehicles can play a key role in transforming